The Impact of Information Technology and Human Resource Empowerment and Its Dimensions - Semyari, Hadi; Sangle, B.R (Management Strategies and Engineering Sciences, 2023)
The objective of this study was to investigate the factors influencing employee empowerment in organizations. A quantitative research design was employed, utilizing a survey method to collect data from 250 employees working in various sectors in Tehran. The survey included validated scales to measure self-efficacy, autonomy, responsibility, job satisfaction, IT familiarity, and employee empowerment. Data were analyzed using descriptive statistics, Pearson’s correlation, and regression analysis to examine the relationships between the variables. The results indicated that self-efficacy, autonomy, and self-confidence were the strongest predictors of employee empowerment. These factors showed significant positive correlations with empowerment, with self-efficacy emerging as the most influential predictor. Job satisfaction and responsibility also contributed to empowerment but to a lesser extent. IT familiarity was found to enhance empowerment by improving work efficiency and providing employees with greater control over their tasks. Regression analysis confirmed that self-efficacy, autonomy, and self-confidence were the key drivers of empowerment, accounting for a significant portion of the variance in empowerment scores. The study highlights the critical role of individual psychological factors such as self-efficacy, autonomy, and self-confidence in fostering employee empowerment. Organizations can enhance empowerment by focusing on training and development initiatives that strengthen employees’ belief in their abilities, increase their autonomy, and boost self-confidence. Additionally, fostering job satisfaction and providing technological resources can further enhance employees’ sense of empowerment, leading to improved organizational outcomes.